Investigation of defect states in light-irradiated single-crystal ZnO by low-temperature positron annihilation lifetime spectroscopy. (1st October 2022) - Nakajima, Makoto; Kinomura, Atsushi; Yabuuchi, Atsushi; Kuriyama, Kazuo
Abstract: Positron annihilation lifetime spectroscopy of single crystalline ZnO during light illumination has been performed in conjunction with electron spin resonance (ESR) to investigate defects related to persistent photoconductivity. The intensity of the ESR signal changes depending on the light wavelengths and the apparent positron lifetime during red-light illumination is approximately 6 ps lower on average than that during blue-light illumination. The results suggest that the excitation of V O during blue-light illumination increases positively ionized V O, while the relaxation of V O during red-light illumination decreases positively ionized V O, leading to a decrease in the apparent positron lifetime.